PENGARUH STRUKTUR ASET DAN PROFITABILITAS TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK TAHUN 2020-2024 - Kania Adinda Putri; Solihin Sidik; Afifa Nurhanifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of asset structure and profitability on debt policy in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This study uses a quantitative approach with an associative research design. The research sample was determined using a purposive sampling technique and obtained 16 companies with a total of 80 observations. The research data used secondary data obtained from the companies' annual financial reports. The data analysis technique used multiple linear regression analysis with the help of IBM SPSS Statistics version 31. Prior to hypothesis testing, the data were tested using classical assumption tests, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that asset structure has a negative and significant effect on debt policy, profitability has no effect on debt policy, and asset structure and profitability simultaneously influence debt policy